UPAYA PERLINDUNGAN HUKUM TERHADAP ANAKKORBAN EKSPLOITASI EKONOMI PADA MASA PANDEMICOVID-19 - Ika Ayuwandari, (2022)
Children have absolute rights that cannot be reduced. With the fulfillment of these rights, children are expected to experience the process of optimal growth and development. However, the issue of the violation of children's rights to date seems endless in various countries. The problem of the violation of children's rights that has so far occurred cannot be separated from the economic exploitation of children. With the entry of the Covid-19 pandemic in the territory of Indonesia, which has a significant impact on all levels of society, it seems that it does not make some parents or individuals who still extort profits from their children. The method used in this research is normative juridical. From the results of this study it was found that the factors that cause economic exploitation of children are: economic factors; public awareness factor; environmental factor; and educational factors. Furthermore, there are efforts that can be made as a form of legal protection related to victims of economic exploitation of children, namely in the form of preventive and repressive efforts. Then from the findings of this study, it is also hoped that the government can pay more attention to the budget launched to the operation of the orphanage where children as victims of exploitative actions get protection, especially after adjusting to online schools during the pandemic. From the community side, it is also expected to be more aware and concerned that children working on the streets such as begging, busking, hawking and so on actually violates the rights that the child should get and is a crime.